Distribution of the invasive pathogenic isolates in blood culture with their antimicrobial susceptibility pattern in diagnostic lab in Karachi - Fatima, Ambreen; Gohar, Hareem; Dawood, Kamran; Sajjad, Mehwish; Fasih, Fatima; Hussain, Zeb (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequent bacterial pathogens causing blood stream infections in various age brackets, and to discover their antibiotic susceptibility pattern. Method: The retrospective, descriptive, observational, cross-sectional study was conducted at the microbiology laboratory of Patel Hospital, Karachi, and comprised positive blood culture bacterial isolates analysed between July 1, 2018, and June 30, 2019. Standard microbiological techniques were employed for the identification and antimicrobial susceptibility testing. Data was analysed using SPSS 20. Results: Of the 3450 specimen, 1243(36%) were positive; 668(53.7%) from male and 575(46.3%) from female subjects, and gram-positive 771(62%) and gram-negative 472(38%). Salmonella typhi was the most common pathogen 139(11.1) among gram-negative organisms, followed by acinetobacter species 103(8.2%), escherichia coli 96(7.7%) and klebsiella species 42(3.4%). Among gram-positive bacteria, the predominant isolates were staphylococcus epidermidis 650(52%), staphylococcus aureus 67(5.4%) and enterococci 28(2.3%). Linezolid (99.8%), vancomycin (99%) and chloramphenicol (69%) were found to be the most sensitive antibiotics among gram-positive cocci. Meropenem (60%), amikacin (46%) and gentamicin (40%) were the most sensitive antibiotics for multidrug resistant gram-negative bacteria. Conclusion: The identification of frequent bacterial pathogens in blood cultures of patients may guide clinicians in proper empirical selection of antibiotics in patients with bacteremia. Key Words: Blood stream infection, BSI, Antibiotic susceptibility, AST, Bacteriological profile, Multi-drug resistance, MDR.